2019
DOI: 10.1002/ecs2.2595
|View full text |Cite
|
Sign up to set email alerts
|

Indicators for assessing tropical alpine rehabilitation practices

Abstract: In this study, we evaluate the effectiveness of indicators for rehabilitation practices in high mountain landscapes that were aimed at increasing grassland palatability and biomass accumulation. Focusing on the department of Huancavelica in Peru, the importance of rehabilitation practiced in this area involves the relationship of alpaca pastoralists and their need to produce wool. Overgrazing in this area has decreased the carrying capacity of the system, which may be problematic for continuing their present l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Vast areas of Páramo land now safe from conflict are not being rapidly protected, making them susceptible to deforestation for cattle and agriculture (Avellaneda-Torres et al, 2020), and illegal logging (Vásquez et al, 2015) and mining (Pérez-Escobar et al, 2018). Thus, improving the current network of protected areas would help minimizing ongoing threats (Duchicela et al, 2019), especially in the highly diverse Páramo complexes of the Eastern Cordillera where putatively new species are still being discovered (Diazgranados and Sanchez, 2017;Mavárez, 2019a). Alongside adoption of mitigation policies, adaptation policies (Elsen et al, 2020) may help safeguarding Páramos.…”
Section: Perspectivesmentioning
confidence: 99%
“…Vast areas of Páramo land now safe from conflict are not being rapidly protected, making them susceptible to deforestation for cattle and agriculture (Avellaneda-Torres et al, 2020), and illegal logging (Vásquez et al, 2015) and mining (Pérez-Escobar et al, 2018). Thus, improving the current network of protected areas would help minimizing ongoing threats (Duchicela et al, 2019), especially in the highly diverse Páramo complexes of the Eastern Cordillera where putatively new species are still being discovered (Diazgranados and Sanchez, 2017;Mavárez, 2019a). Alongside adoption of mitigation policies, adaptation policies (Elsen et al, 2020) may help safeguarding Páramos.…”
Section: Perspectivesmentioning
confidence: 99%
“…This suggests that changes in community composition are rapidly taking place while gain or extinction of species takes a longer duration to manifest (Milchunas & Lauenroth, 1993 ). This difference is most likely due to changes in abundance of species with particular traits in grazing treatments (Duchicela et al., 2020 ). For example, previous studies in South American mountainous grasslands have shown that grazing is associated with a reduction in dominance of palatable species, such as short grasses species with higher specific leaf area (SLA) and an increase in abundance of tolerant species, with higher leaf dry matter content (LDMC) such as cushion and prostate grasses (Diaz et al., 2004 ; Sandoval‐Calderon et al., 2023 ).…”
Section: Discussionmentioning
confidence: 99%